A measure for perceived social support for university students: Implication for campus leaders - Norfaezah Md Khalid; Melati Sumari; Norsafatul Aznin A. Razak; Ahmad Shamsuri Muhamad; Hamidah Sulaiman (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
Social support plays a crucial role in an individual's life. Individuals who experience strong, positive social relationships and feel supported by others tend to report lower levels of anxiety, depression, and psychological stress. Social support may come from family members, friends, and significant others in life. Looking at the importance of social support in university students’ lives, there have been a few scales to measure social support, and one of them is the Multidimensional Perceived Social Support Scale, which was developed in a Western country. This study examined the validity of the Malay version of the Multidimensional Perceived Social Support Scale in a sample of 443 Malaysian university students. Results support the high reliability and validity of this scale. Confirmatory factor analysis reported the expected three-factor structure and a high correlation between factors and scales. In addition, internal consistency was good, and correlation analysis with the Satisfaction with Life Scale proved the theoretical relations among the constructs. The findings suggest that MPSS-M is a reliable and valid tool to measure social support among students in higher education institutions. Campus leaders and student affairs professionals may use the scale to identify the source of support among students. Implication for university management is also discussed.